Evaluation and improvement of security using penetration testing (pentest) methods of host-based intrusion detection system (hids) and intrusion detection system (ids) at the Sei Sekambing C II village office - Mara Sakti Siregar; Furqan Khalidy; Mardiah Mardiah (Jurnal Sains, Teknologi & Komputer, 2026)
The rapid development of information technology demands a strong and reliable network security system, especially in government agencies that manage important public data. The Sei Sekambing C II Village Office has utilized computer networks to support public service activities, but still faces various network security risks, such as illegal access, malware, and system vulnerabilities. This study aims to evaluate and improve network security using penetration testing methods, as well as the implementation of an Intrusion Detection System (IDS) and a Host-based Intrusion Detection System (HIDS). The results of the study revealed several security vulnerabilities, such as insecure File Transfer Protocol (FTP) services, excessive open ports, and successfully detected brute force attacks. After improvements in the form of patching, migrating FTP services to Secure File Transfer Protocol (SFTP), and updating IDS/HIDS signatures, the level of network security experienced a significant increase with a reduction in vulnerabilities of up to 66%. This method has proven effective in strengthening network security infrastructure in government environments.